Characterisation and research of the milk quality in Krk cheese manufacturing - Neven Antunac; Nataša Mikulec; Darija Bendelja; Zvonimir Prpić; Zdravko Barać (Mljekarstvo)
Physical-chemical composition and hygienic quality of milk are of crucial importance in cheese manufacturing. During 2007, a research was carried out with the aim to investigate manufacturing features and milk quality of Krk sheep and to describe technological procedure of manufacture and physicalchemical composition of Krk cheese. The milking capacity was checked according to AT method. Chemical composition was analyzed by infrared spectrometry and hygienic milk quality by fluoro-opto-electronic method, i.e. flow cytometry method. In 160 days of lactation, sheep produced in average 108 kg of milk (38 kg in lactating and 70 kg in milking period), 5.67 kg of milk fat and 4.12 kg of proteins. In the average, the milk contained: 19.49 % of dry matter, 8.29 % of milk fat, 5.99 % of proteins, 4.45 % of lactose and 11.32 % of dry matter without fat. Milking had a significant influence on: daily milk quantity, dry matter and milk fat share, milk freezing point and hygienic milk quality (log10MO and log10BSS). Significant correlation coefficients were determined between manufacturing features of sheep and certain milk quality indicators. Based on the research results, values of physical-chemical composition, microbiological and sensory milk and cheese quality can be suggested, necessary in standardization of technological manufacturing procedure of Krk cheese.